Muslim and Democracy: A Reflection from 2012 Aceh’s Gubernatorial Election - Irfan Iryadi; Mursyidin Zakaria; Effendi Hasan; Dedy Tabrani; Fadhil Ilhamsyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This paper explores about governor election in Aceh period 2012-2017 as a socio-political lesson. At that moment, political trends in Aceh are ongoing mass politics, not politics ideology based on the interests of the people. Mass politics is crewed politics on the basis of pragmatic and opportunist ideology. Intimidation and massive mobilization of the masses accompanied by money politics and imagery are characteristic of mass politics. In mass politics the potential for conflict is also quite high. Not often people who are victims. People admits that gubernatorial election of Aceh in 2012  was won by Zaini Abdullah and Muzakkir Manaf (Zikir) carried out by local political parties, namely the Party Aceh, the legislature is complete and the executive is entirely in the hands of the Party's control Aceh. All his potions and political teachings will be lowered to the service arena for Acehnese people during the 2012-2017 period. But the question then blocks in all of our minds, will the opposition be still dare to survive with the political dialectic recently? Of course we can see this at least in the first six months post the inauguration of Zikir as governor and deputy the governor of Aceh later.